2018
DOI: 10.1039/c8pp00137e
|View full text |Cite
|
Sign up to set email alerts
|

A naked-eye fluorescent sensor for copper(II) ions based on a naphthalene conjugate Bodipy dye

Abstract: A novel naphthalene-Bodipy dye (N-Bodipy) was designed, prepared and characterized. N-Bodipy showed a selective and sensitive recognition toward Cu(ii) ions as a fluorescent antenna group in acetonitrile/water over other metal cations. The complexation between Cu(ii) ions and N-Bodipy gave a specific color change as well as caused fluorescence quenching under long-wavelength light (365 nm). The remarkable quenching effect in fluorescence intensity centered at 538 nm was only observed in the presence of copper(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…The authors also reported theoretical calculations and biological studies and the practical applicability of the sensors in the living cell. Baslak et al . developed a Cu (II) ion sensor in acetonitrile/water.…”
Section: Detection Of Copper By Sensing Technologymentioning
confidence: 99%
“…The authors also reported theoretical calculations and biological studies and the practical applicability of the sensors in the living cell. Baslak et al . developed a Cu (II) ion sensor in acetonitrile/water.…”
Section: Detection Of Copper By Sensing Technologymentioning
confidence: 99%
“…[25][26][27] Recently, a few colorimetric sensors for Cu 2 + have been also reported. [28][29] These sensors also suffer from long response time, poor selectivity, complex organic synthesis, and poor detection limits. [30] Nowadays, Schiff base derivatives are increasingly used as colorimetric sensors due to their simple synthesis steps and high selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…But, many have some limitations, such as having a weak detection limit and complex synthesis steps . Recently, a few colorimetric sensors for Cu 2+ have been also reported . These sensors also suffer from long response time, poor selectivity, complex organic synthesis, and poor detection limits .…”
Section: Introductionmentioning
confidence: 99%
“… 22 24 So far, many fluorescent probes for Cu 2+ ions have been reported. The development of new fluorescent probes is, however, still being concerned due to the limitations of reported probes such as low sensitivity and selectivity, 25 , 26 a narrow range of pH, 20 , 27 29 working in solutions with a high proportion of organic solvents, 26 , 30 and excitation wavelength in the ultraviolet region. 26 , 28 , 31 , 32 These limitations reduce the application of probes to monitor Cu 2+ ions in living cells.…”
Section: Introductionmentioning
confidence: 99%